Anti-inflammatory Compounds Camphor and Methylsalicylate from Traditionally Used Pain Curing Plant Equisetum arvense L. - Adhikari, Achyut; Bhandari, Silan; Pandey, Durga Prasad (Journal of Nepal Chemical Society, 2019)
Equiseum arvense L. is a bushy perennial herb commonly called field horsetail distributed in the northern part of Nepal and used against curing muscle and bone pain and other many diseases. This research work was performed to analyze the possible cause of the anti-inflammatory activity of this plant. Out of four different fractions, dichloromethane (DCM ) fraction showed the presence of compounds on TLC and was subjected to column chromatography to isolate and identify pure compounds. D2 and D20 fractions eluted from column gave single and distinguished spots so that these fractions were subjected to gas chromatography analysis. The GC analysis of the pure fraction D2 obtained from column revealed the presence of a major compound major compounds camphor (92.53%) and other minor compounds; (+)-2-Bornanone, Camphor, Carvone<(z)-, dihydro->, Benzoic acid, 2-(1-oxopropyl)- and GC report from D20 fraction showed two compounds; Salicylate<methyl-> and Benzoic acid, 2-(1-oxopropyl)-. The major compounds camphor (92.53%) and methyl salicylate (66.87%) have been reported being potent anti-inflammatory activity and their synergetic effect is more prominent for the same.